Antibiotic resistance, putative virulence factors and curli fimbrination among Cronobacter species. (November 2019) - Odeyemi, O.A.; Abdullah Sani, N.
Abstract: This study aimed to investigate antibiotic resistance and putative virulence factors among Cronobacter sakazakii isolated from powdered infant formula and other sources. The following 9 cultures (CR1-9) were collected from our culture collection: C. sakazakii and 3 Cronobacter species: C. sakazakii ATCC® 29544™, C. muytjensii ATCC® 51329™, C. turicensis E866 were used in this study. Isolates were subjected to antibiotic susceptibility and the following virulence factors (protease, DNase, haemolysin, gelatinase, motility and biofilm formation) using phenotypic methods. All the bacteria were able to form biofilm on agar at 37 °C and were resistant to ampicillin, erythromycin, fosfomycin and sulphamethoxazole. It was observed from this study that tested strains formed weak and strong biofilm with violet dry and rough (rdar), brown dry and rough (bdar), red mucoid and smooth (rmas) colony morphotypes on Congo red agar. Rdar expresses curli and fimbriae, while bdar expresses curli. Both biofilm colony morphotypes are commonly found in Enterobacteriaceae including Salmonella species. This study also reveals a new colony morphotypes in Cronobacter species. Conclusively, there was correlation between putative virulence factors and antibiotic resistance among the tested bacteria. Further study on virulence and antibiotic resistance genes is hereby encouraged. Highlights: Antibiotic resistance and putative virulence factors among Cronobacter was investigated Isolates formed weak and strong (, and ). expresses and, expresses. This study also reveals a new colony in Cronobacter species.